Reperfusion Time of STEMI Patients in Indonesia and Outside Indonesia - Muhammad Fachriyan Romadhona; Yudi Her Oktaviono; Sundari Indah Wiyasihati; Rosi Amrilla Fagi (Cardiovascular and Cardiometabolic Journal (CCJ), 2023)
Highlights: 1. The median of door-to-ballon in handling STEMI and total ischemic time is longer in Indonesia than other countries. - Background: STEMI is a medical emergency that requires quick treatment. Several problems might arise from the improper and delayed treatment of STEMI patients. Objective: This study aimed to examine the differences in the reperfusion time of STEMI patients in Indonesia and outside Indonesia. Method: Systematic Review method is used without meta-analysis. The variables to be studied in this study are Door-to-Balloon time and Total Ischemic Time. PubMed, Science Direct, and Scopus are used as search tools using the MeSH terms and keywords that have been determined to look for articles within 2017 – 2020. The selection of the literature that has been obtained was carried out according to the PRISMA algorithm. Results: Twelve journals were used that were relevant, compatible, and following the inclusion and exclusion criteria. It was found that the median door-to-balloon in handling STEMI in Indonesia ranged from 70 to 94 minutes, while the median total ischemic time ranged from 275 to 461 minutes. Meanwhile, the median door-to-balloon time and total ischemic time outside Indonesia ranged from 41 to 87 minutes and 112 to 273 minutes, respectively. Conclusion: In conclusion, the median and average door-to-balloon time and total ischemic time in Indonesia are longer than the door-to-balloon time and total ischemic time outside Indonesia in handling STEMI.